Electroluminescence imaging of organic photovoltaic modules - Hoyer, U.; Wagner, M.; Swonke, Th.; Bachmann, J.; Auer, R.; Osvet, Andres; Brabec, Christoph (Applied Physics Letters, 2010)
We report on electroluminescence (EL) imaging of organic photovoltaic cells and modules with poly(3-hexylthiophene)/[6,6]-phenyl C61 butyric acid methyl ester as semiconductor layer. The dominant EL emission is found in a spectral regime between 1200 and 1400 nm and is identified as the radiative decay of the charge transfer complex formed between the polymer and the fullerene. Electroluminescence emission from the pristine compounds is either much weaker or completely absent. Overall, electroluminescence imaging is shown to give valuable information on the defects but also on the performance of organic solar modules. © 2010 American Institute of Physics.